Pregnancy outcomes of a small cohort with unexplained antepartum haemorrhage at Aberdeen Maternity Hospital. (16th November 2010) - Haque, L; Fatima, F; Mathur, M
Abstract : Unexplained minor ante partum haemorrhage (APH) occurs in about 5% of pregnancies and can cause perinatal morbidity and mortality. The authors identified cohort of 50 consecutive cases with unexplained minor APH over 2 month period. Here 66% had one, 22% had two and 2% of women had more than two episodes of unexplained APH, 2% had a small for date fetus. Spontaneous vaginal delivery (SVD) was achieved by 60% women, while labour was induced in 16% of women induction of labour (IOL) for 12% at term and 4% before 37 weeks, they all achieved vaginal delivery), 24% had lower segment caesarian section (LSCS) (12% had emergency LSCS after going into spontaneous labour for fetal distress and 12% women had elective LSCS for previous LSCS, malpresentations. The majority delivered after term, 12% delivered between 32 and 36 weeks. Babies weighing less than 2.5 kg were 12%. The apgar score was good for majority. Neonatal admission was 8% and these were babies of mothers with single episode of APH. The authors can say that there are no significant changes in pregnancy course or neonatal outcomes when compared with literature searched. Therefore the authors need to evaluate whether to intervene in cases of minor unexplained APH as there is limited role for prophylactic elective delivery in the fetal interest.